(3GdhQO GdCfSi hGdhGQO GdbOSi aj JQLeI GdYGQa HGddg YHO GdZfi GdfGHdSis - (3eMeO Hf eMeO Hf TQja Hf TeS GdOjf eMeO Hf YHO GdQMef GdZRj GdYGeQj GdMSjfj GdOeTbj GdUOjbj, CHh GdaVd ceGd GdOjf,J (B1214 (3g` s ((3YHOGdcQje GdMeRGhi s)
(3ChdgG (B:s
(3eG HYO jbhd GdYHO ceGdG dOjf Ef LO hGdOi dCeg GdYGde GdQHGfi s
(3BNQgG (B:s
(3gPG eG hLO HfSNI eDdag GdgeGe s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B71s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B473 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B334 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs